EKOSISTEM PENDIDIKAN: SOLUSI DEMOKRATISASI PENDIDIKAN - Sugiyar Sugiyar (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2017)
Education has a strategic role to increase the quality of human resources. A qualified person is fulfilled by its cognitive, affective, and psychomotor dimensions. The fulfillment of these dimensions proportionally creates an intelligent and competitive person. Spiritual, emotional and social intelligent were capable of forming a whole person, able to adapt and socialize with people in their various backgrounds. Education as a system offers various syner-gistic elements to achieve the ideal educational goals. The unity of the educational system or educational ecosystem will contribute effectively to educational result in the global era. The elements of the educational ecosystem have their own roles to contribute for the realization of democratic educa-tion. Democratization of education is needed, so that educa-tion fulfills the needs of large community. Education beco-mes shared responsibility on central government, local government, and society. Education as the basic needs of the community, then all stakeholders of education should sit together to formulate a qualified and marketable education in a sustainable manner.Key words: Educational Ecosystem, Democratization